Advances in Understanding the Physiological and Molecular Responses of Sugar Beet to Salt Stress - Lv, Xiaoyan; Chen, Sixue; Wang, Yuguang (Frontiers in Plant Science, 2019)
Soil salinity is a major environmental stress to crop growth and productivity. A better understanding of molecular and physiological mechanisms underlying salt tolerance will facilitate efforts to improving crop performance under salinity. Sugar beet is considered as a salt tolerant crop, and it is therefore a good model for studying salt acclimation in crops. Recently, many determinants of salt tolerance and regulatory mechanisms have been studied using physiological and ‘omics approaches. This review provides an overview of recent advances in sugar beet response and tolerance to salt stress. We summarize the physiological and molecular mechanisms, including maintenance of ion homeostasis, accumulation of osmotic-adjustment substances and antioxidant regulation. We focus on progresses in deciphering the mechanisms using ‘omics technologies, and describe key candidate genes involved in the sugar beet salt tolerance. Understanding salt stress response and tolerance of sugar beet will enable translational application to other crops, and thus has significant impacts on agricultural sustainability and global food security.